2021
DOI: 10.3390/nano11081938
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Polyphenols from Lycium barbarum Leaves into Liposomes as a Strategy to Improve Their Delivery

Abstract: This study is focused on the encapsulation of polyphenols from Lycium barbarum leaves into liposomes as a strategy to improve their delivery. Liposomes loaded with Lycium barbarum leaves extract were obtained and characterized for particle size, polydispersity, entrapment efficiency, and stability. Liposomes presented entrapment efficiency higher than 75%, nanometric particle size, narrow polydispersity, and good stability over three months at 4 °C. The liposomes containing Lycium barbarum offered a slower rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Further, Yücel et al [ 39 ] reported liposomal EE of 62% for rosmarinic acid prepared by the dry film hydration method using dipalmitoyl phosphatidylcholine and cholesterol. Liposomes were also found to be an appropriate encapsulation technique for Polygonum aviculare L. extract [ 40 ], Glycyrrhiza glabra L. roots extract [ 41 ], and Lycium barbarum L. [ 42 ] leaves extract, achieving EE of 83, 84 and 84.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Yücel et al [ 39 ] reported liposomal EE of 62% for rosmarinic acid prepared by the dry film hydration method using dipalmitoyl phosphatidylcholine and cholesterol. Liposomes were also found to be an appropriate encapsulation technique for Polygonum aviculare L. extract [ 40 ], Glycyrrhiza glabra L. roots extract [ 41 ], and Lycium barbarum L. [ 42 ] leaves extract, achieving EE of 83, 84 and 84.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols from goji berries’ leaves have been encapsulated in liposomes to improve their delivery in terms of sustaining their release, and avoiding the burst effect compared to the dissolution of the free extract [ 151 ]. The obtained liposomes have successfully served as carriers for polyphenols and demonstrated a cytoprotective effect on L-929 mouse fibroblasts cells.…”
Section: Processing Of Goji Berriesmentioning
confidence: 99%
“…Limitations come into being if employing extracts from Goji leaves directly due to the poor solubility, toxicity and degradation in a gastrointestinal medium (Pavaloiu et al ., 2021). To deal with this, one of the strategies is to encapsulate the extracts into emerging drug delivery systems (Yadav et al ., 2014).…”
Section: Potential Applications Of Goji Leaves In the Food Industrymentioning
confidence: 99%
“…Pavaloiu et al . (2021) prepared the liposomes loaded with polyphenolic extracts from LBL. Liposome encapsulation promoted the delivery of LBL extracts.…”
Section: Potential Applications Of Goji Leaves In the Food Industrymentioning
confidence: 99%